STUDENTS' PERCEPTIONS AND MOTIVATION TOWARD E-LEARNING AT AKM HIGH SCHOOL DURING THE COVID-19 PANDEMIC - Anggrisia, Nur Fitria; Islami, M. Fadel Ihza (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
The use of media in online learning became essential during the Covid-19 pandemic, necessitating a shift to remote education across Indonesia. As a solution to maintain educational continuity, e-learning emerged as an effective tool, especially in supporting English language instruction. This study explores the perceptions and motivations of eleventh-grade students at AKM High School (pseudonym) toward e-learning in their English classes during the 2020/2021 academic year. Data gathered through questionnaires and interviews revealed that 50.1% of students agreed that teachers effectively delivered lessons via e-learning, while 60.94% found the curriculum aligned with their syllabus expectations. Notably, 44.5% of students felt that e-learning improved their English skills, with 41.7% strongly agreeing that teachers facilitated productive question-and-answer sessions. Regarding motivation, 69.4% of students responded positively to the instructional media, 58.3% felt encouraged to ask questions, and 61.1% were motivated to complete assignments. However, only 50% remained motivated without assignments, and 58.3% expressed a sustained enthusiasm for English learning through e-learning. The findings suggest that students generally perceive e-learning as flexible and effective, though challenges such as procrastination emerged. Overall, e-learning has proven to be a viable alternative, fostering positive attitudes and motivation for learning from home during challenging times.